Bad blood [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels., 2010)
In southern Minnesota, a young man murders a local farmer, drops the body into a grain bin, and then calls the sheriff to report the "accident." Suspicious, the sheriff calls in Virgil Flowers, who quickly breaks the kid down. The next day the boy is found hanging in his cell. Virgil suspects foul play, and as he investigates, he begins to uncover a multigeneration, multifamily conspiracy--a series of crimes of such monstrosity that even he has difficulty in comprehending it.